Proyecto de Factibilidad para la Producción de Queso Empacados al vacío en la Parroquia Valladolid y su Comercialización en la Ciudad de Loja - Minga Arévalo, Omayra Karla (2017)
The present research work has the objective of elaborating a feasibility project for the creation of a company producing and selling Vacuum Packed Cheese, whose purpose is to take advantage of the existing resources in the Valladolid parish and benefit the finished product to the inhabitants of The city of Loja, also raised five specific objectives that are; Conduct the market study, technical study, administrative - legal study, financial study and financial evaluation. In order to meet these objectives, methods, techniques and procedures were used to investigate and verify the veracity of the project. The methods used were: Inductive method, deductive method, survey and interview techniques. The study contemplates 4 chapters that are detailed below: Market Study: This study was used to make the decision on the introduction of the new cheese to the market, the first step is to identify the target market for the product in this case is the urban population of the city of Loja comprised 49,803 Families. Then the potential demand was determined 90,641 cheeses vacuum packed and a 95% acceptance of the new company, through the surveys that were applied in different sectors of the city. In addition, it is announced the classification and nature of the product to be elaborated, concluding with the description of the marketing mix that the company is going to make so that the new product is known in the market by the consumers. Technical Study: The size of the project was determined, with an installed capacity of 75% of 63,360 cheeses packaged in annual vacuum, and with a percentage of 55% capacity used with a value of 47,520 cheeses packaged in vacuum per year. The location and physical distribution of the company was established; As the engineering of the project that corresponds to the description of the production process of cheeses vacuum packed and the raw materials necessary for their elaboration. Administrative-Legal Study: A limited liability company was formed, whose corporate name is: "QUESOS YANELA Cía. Ltda. "; Which will have a useful life of 5 years. In order for the company to efficiently carry out its activities, an administrative structure was created to allow an adequate use of resources; Through the elaboration of the hierarchical levels, as well as of the structural, positional and functional organizational charts; In addition to the function manuals for each position. Financial Study: The budgets of fixed assets, deferred assets, working capital, which gave a total investment of $ 56,360, a value that will be financed with a capital of partners of $ 48,160 and a credit of $ 8,200 granted by the BanEcuador And all financial statements as they are; Cost budgets, with a total of $ 75,441.45 for the first year, revenue budgets determining the unit cost of production $ 1.59, plus a 36% profit margin, resulting in a retail price of $ 2.80 . For the break-even point, we classified the fixed and variable costs obtaining as a result for the first year, according to the installed capacity of 42.47% and based on sales of $ 53,274.18, at this point the company does not earn Neither loses. Financial Assessment: For the evaluation of the project the Net Present Value (NPV) was calculated, which gave a value of $ 114,855.25, the Internal Rate of Return (TIR) is 77%, the Capital Recovery Period (PRK) , Is one year, eight months and one day, the Cost Benefit Ratio is $ 1.22, which means that for every dollar invested the company will get 22 cents of profit, and the sensitivity analyzes show that the project will support A maximum cost increase of 54% and a maximum income reduction of 30%. With all the above, it has been demonstrated that the project in question is feasible and therefore it is recommended to implement the company in the parish of Valladolid and its commercialization in the city of Loja.